ECB-(RE)BASE: Heterogeneity in expectation formation and macroeconomic dynamics - Stéphane Adjemian; Nikola Bokan; Matthieu Darracq Pariès; Georg Müller; Srečko Zimic (European Central Bank (ECB), 2024)
This paper introduces ECB-(RE)BASE as the model-consistent, or rational expectation version of the ECB-BASE model. It brings new analytical capabilities to consider varying degrees of heterogeneity in expectation formation across the agents of the model. While the original version of ECB-BASE features VAR-based expectations, we examine two alternative versions either with full model-consistent expectations or with hybrid expectations. The paper provides a didactic exposition of the changes in the model properties brought by the various expectation settings. Furthermore, we conduct illustrative scenarios around the macroeconomic shocks experienced over the recent years. The simulations notably suggest that moving from VAR-based to model-consistent expectations would limit the pandemic-induced macroeconomic volatility but would exacerbate the price pressures during the inflation surge period. Overall, this model development extends the range of possibilities for risk and policy analysis which can enhance the contribution of ECB-(RE)BASE to monetary policy preparation.
Keywords: C3; C5; E1; E2; E5; 330; Semi-structural model; model-consistent expectations; euro area; monetary policy